2022
DOI: 10.1080/22221751.2022.2065932
|View full text |Cite
|
Sign up to set email alerts
|

N-chlorotaurine is highly active against respiratory viruses including SARS-CoV-2 (COVID-19) in vitro

Abstract: N -chlorotaurine (NCT) a long-lived oxidant generated by leukocytes, can be synthesized chemically and applied topically as an anti-infective to different body sites, including the lung via inhalation. Here, we demonstrate the activity of NCT against viruses causing acute respiratory tract infections, namely severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), influenza viruses, and respiratory syncytial virus (RSV). Virucidal activity of NCT was tested in plaque assays, confirmed by RT-qPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
1
8
0
1
Order By: Relevance
“…According to the results of another study by our group [ 21 ] it was found that out of forty-four studied Candida strains, four (two C. glabrata , one C. albicans ) were characterized as susceptible dose-dependent, and two ( C. glabrata ) were found to be resistant to fluconazole. Due to the unspecific oxidizing/chlorinating mechanism of action of active chlorine compounds and confirmed previous studies against different kinds of pathogens, none of the studied Candida strains showed resistance to NCT [ 37 , 39 , 42 , 43 ]. Therefore, the use of NCT as an alternative antiseptic is also important in the treatment of VVC caused by fluconazole-resistant Candida strains.…”
Section: Discussionsupporting
confidence: 84%
“…According to the results of another study by our group [ 21 ] it was found that out of forty-four studied Candida strains, four (two C. glabrata , one C. albicans ) were characterized as susceptible dose-dependent, and two ( C. glabrata ) were found to be resistant to fluconazole. Due to the unspecific oxidizing/chlorinating mechanism of action of active chlorine compounds and confirmed previous studies against different kinds of pathogens, none of the studied Candida strains showed resistance to NCT [ 37 , 39 , 42 , 43 ]. Therefore, the use of NCT as an alternative antiseptic is also important in the treatment of VVC caused by fluconazole-resistant Candida strains.…”
Section: Discussionsupporting
confidence: 84%
“…However, interestingly, DTNB and bio-IAM methods showed that NCT was more efficient in producing cysteine oxidation compared to the same concentrations of H 2 O 2 . This difference can be explained by the specificity of NCT in oxidizing cysteine and methionine residues and chlorinating tyrosine, phenylalanine, histidine, and tryptophan ones and amino groups ( Peskin and Winterbourn, 2001 ; Eitzinger et al., 2012 ; Lackner et al., 2022 ), while H 2 O 2 has a broad and unspecific effect ( Fligiel et al., 1984 ). Cofilin 1 cysteine residues are susceptible to oxidation by NCT and H 2 O 2 ( Klemke et al., 2008 ; Klamt et al., 2009 ; Luo et al., 2014 ; Cameron et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…NCT is a chlorinated amino acid derived from taurine, that is naturally produced by human leucocytes and has antiseptic properties (Gottardi and Nagl, 2010). Additionally, NCT has a limited spectrum of reactivity targeting most cysteine and methionine residues, aromatic amino acids, and amino groups of the proteins (Peskin and Winterbourn, 2001;Eitzinger et al, 2012;Lackner et al, 2022). In contrast, a similar mechanism induced by H 2 O 2 usually damages proteins (Fligiel et al, 1984) and other biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…HOCl and NCT have anti-inflammatory properties which lead to reduced local inflammation, lower infectivity through reduced permeability, and perhaps lower morbidity and mortality overall [ 48 ], [ 49 ]. The verified unique stability and low-level reactivity of NCT are considered essential for both its function in the mammalian defense system and its practical applicability, which manifests itself in an optimal compromise between microbiocidal activity and toxicity [ 50 ], [ 51 ].…”
Section: Hocl – a Natural Biocidementioning
confidence: 99%